Industrial training report: KPJ Pahang Specialist Hospital / Ahmad Fazri Kamarul Zaman - Kamarul Zaman, Ahmad Fazri (Perpustakaan Tengku Anis, 2018)
Abstract: The special project is created based on the problem that has been observed since trainee started the industrial training from 1st February until 30th June 2018 in Health Information Management Services (HIMS) at KPJ Pahang Specialist Hospital. Trainee has been placed at HIMS under supervision of Miss Tengku Rusidah Binti Tuan Long and she is HIMS Officer that is responsible for the HIMS Department. After that, trainee has been assigned to observe the work process in the department because HIMS is one of the important clinical support departments in the hospital because they need to maintain the patient records or they-called it as 'folder’. After a month, trainee has determined the problems faced by HIMS Staff, that affected others department such as missing folder, folder cannot he trace by staff when other departments request for the folder. After that medical report staff always late in calculating the statistics for the completed medical report that they must submit to operation manager every month. So trainee has decided to develop one system named as Meditouch System that can-assist staff in tracking the folder and track all medical report requested and able to generate the report from the medical report. The current manual system are not effective because they only wrote it into the paper if there any request for the folder from clinic and same goes to the medical report. Throughout the industrial training, trainee is able to improve skills in communication especially when need to face the patient, learn the new working environment and apply all the theories that has been learning during studies, The. industrial training session is going well until the end and the staff in KPJ Pahang Specialist Hospital gave a very good cooperation to the trainee during the industrial training.